The approach in recording the phenomena of the solar and lunar eclipse through some Mamluk sources - يحيى العامر, أحمد (Al-Adab Journal, 2018)
This study examines the two phenomena of the solar and lunar eclipse though three Mamluke sources which are Badāʼiʽ al-zuhūr fī waqāʼiʽ al-duhūrof Ibn Iyās, Kitāb al-Sulūk li-ma‘rifat duwal al-mulūk of Maqrīzī and Kitāb al-Nuğūm al-zāhira fī mulūk Mișr wal-l-Qāhira of Ibn Taġrī Burdī. We will count in this research all the solar and lunar eclipse noted in these sources. We are going to examine also the methods of the historians in their notation and we will compare them to verify the precision of the mention of these phenomena through the modern registers of lunar and solar eclipses.